2016
DOI: 10.1080/14992027.2016.1178859
|View full text |Cite
|
Sign up to set email alerts
|

Educating teenagers about hearing health by training them to educate children

Abstract: Providing training to teenagers had benefits beyond the delivery of training to younger children, but improvements in the delivery model may increase the uptake and impact on the teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
9
0
10
Order By: Relevance
“…Interventions towards safer hearing behaviour have been shown to be effective in young children [ 47 , 48 ], but in teenagers are less effective [ 47 ] or non-significant [ 49 ]. Effects on teenagers were sustained only when interventions involved them more deeply in the process [ 50 , 51 ]. This is consistent with the power of the influences described here.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions towards safer hearing behaviour have been shown to be effective in young children [ 47 , 48 ], but in teenagers are less effective [ 47 ] or non-significant [ 49 ]. Effects on teenagers were sustained only when interventions involved them more deeply in the process [ 50 , 51 ]. This is consistent with the power of the influences described here.…”
Section: Discussionmentioning
confidence: 99%
“…For such guidance to be effective, each individual must understand what they are told in order to reconsider their personal habits and accept such information and start to rethink about their habits and change them into healthier ones (29,30) . However, only providing information about the dangers caused by certain choices do not necessarily have any effect on the population.…”
Section: Discussionmentioning
confidence: 99%
“…of loudness may occur over the life course, with children being less deeply conditioned than teenagers, and not yet acculturated, and thus more open to influence. In research where intervention effects on self-reported behavior in teenagers were sustained, 52,53 interventions were more elaborate, and yet effect sizes could still be improved.…”
Section: Implications For Hearing Healthmentioning
confidence: 99%